Africa's passive revolution: crisis in Malawi. Issue 3 (6th May 2016) - Brooks, Andrew; Loftus, Alex
Abstract : Recent protest movements in sub‐Saharan Africa have generally failed to effect progressive transformations. Efforts to achieve social change have been frustrated by governing elites that continue to utilise their vacillating and unequal relationships with the external environment to sustain power. Although the leading figures may change, the dominant African class can re‐establish leadership through new alliances with domestic and international networks of capital. To understand such 'change‐without‐change', this paper contributes to the growing body of literature on Antonio Gramsci's development of 'passive revolution'. The comparative character of Gramscian analysis enables his philosophy of praxis to be translated into very different historical and geographical settings. With this in mind we draw together recent engagements with passive revolution from Geography, Politics and African Studies. In particular we develop Jean‐François Bayart's notion of extraversion, while considering it in relation to more recent philological engagements with Gramsci. Our empirical focus is the politics of transition in Malawi. In his second term in office, the autocratic and unpopular president, Bingu wa Mutharika, implemented economic policies that ran against neoliberal orthodoxy and suppressed protest during a period of crisis. Mutharika was replaced, following his death in 2012, by Joyce Banda, a previously marginalised vice‐president, who nurtured a re‐engagement with transnational capital. Working through the state, Banda led a transformation from on high and moved to impose new economically liberal policies, including a major currency devaluation, which reduced living standards for many. We draw our empirical material from Chancellor College, a major site of protest against Mutharika in 2011. Evidence from interviews with staff and students demonstrates how two episodes of revolution/restoration in Malawi, a country distant from the western historical experience, can be interpreted through Gramsci's socially differentiated understanding of politics.